Interpretation of Al-Baqarah Verse 221 Forbidding the Marriage of Unbelievers - Irwan Ramadhani; Nerisma Eka Putri (Dialogia, 2024)
In the contemporary era, tafsir has evolved, leading to diverse methods and patterns, reflecting its nature as a human endeavor that develops across generations. One example is Allah's prohibition of marriage between believers and idolaters, which continues to draw scholarly interest. Researchers explore this verse to understand its meaning, context, and application, particularly in relation to Indonesian legal principles. This study, using library research and a qualitative approach, examines the prohibition of interfaith marriage in Surah Al-Baqarah, verse 221, based on Tafsir Ibnu Katsir and Tafsir Al-Misbah. The findings align with Indonesian law, specifically Article 2, paragraph (1) of Act No. 1 of 1974 on Marriage and its amendment under Law No. 16 of 2019, both of which affirm that marriages are only valid if conducted according to the religious rules of the individuals involved, thus prohibiting interfaith marriages.